A fast and efficient algorithm for acoustic resonances of a 3D open cavity with asymmetrical walls. (February 2021) - Zhai, Qingbo; Ning, Fangli; Ding, Hui; Liu, Zhe; Zhang, Changtong; Wei, Juan
Abstract: Cavities with asymmetrical walls exist in many industrial applications and its acoustic properties are crucial to noise and vibration control. However, traditional methods are complex and time-consuming such as finite element method (FEM). Given the problems existing in traditional methods, the ISM-TM algorithm which combined the image source model (ISM) with the transformation matrix (TM) is proposed to explore acoustic resonances of a 3D open cavity with asymmetrical walls in this work. Compared with experiments, the proposed algorithm can well obtain the acoustic resonances of a 3D open rectangle cavity and a 3D open cavity with non-parallel walls. In a 3D open rectangle cavity, with the increase of the calculation frequency, the relative error between acoustic resonant frequencies measured by experiments and estimated by the ISM-TM is reduced from 11.3 % to 0.9 % . In a 3D open cavity with non-parallel walls, with the increase of the calculation frequency, the relative error between acoustic resonant frequencies measured by experiments and estimated by the ISM-TM is reduced from 2.3 % to 0.2 % . The results suggest that the proposed algorithm in this work could well estimate acoustic resonances of a 3D open cavity for medium and high frequency. Compared with the FEM, the proposed algorithm can provide the frequency response function (FRF) of any point in a 3D open cavity easily and quickly. The ISM-TM can be used to guide cavity design to predict possible acoustic resonances in the cavity in advance.